Influence of Teachers’ Self-Efficacy and Attitude towards the Integration of ICT into Teaching and Learning at the Basic School Level - Arhin, David; Kwakye, Kwabena; Quaynor, Leonard Quayetey; Boakye, Ruth Osei; Yeboah, Jemima Afrah (American Journal of Education and Practice, 2022)
Background: ICT has become crucial in our everyday life and for that matter teaching and learning. It is, therefore, imperative to examine its involvement in education. Purpose: The current study sought to explore the influence of teachers' self-efficacy and attitude towards the integration of ICT into teaching and learning at the basic school level. Method: The study was a descriptive survey with a sample size of 159 teachers representing 270 accessible population which was purposively located. Respondents responded to the questionnaire via an online survey in the quest for data collection. Data to answer research questions and test research hypotheses were analyzed using frequencies, percentages, means, standard deviations, and Pearson Product Moment Correlational Coefficient. Findings: The study revealed that most teachers have a high level of self-efficacy. The study also found that majority of the teachers have positive attitudes toward the integration of ICT in teaching and learning. However, it was revealed that there is a significant difference between male and female teachers' attitudes towards the integration of ICT in teaching and learning. Finally, there is no significant relationship between self-efficacy and teachers' attitudes toward the integration of ICT in teaching and learning. Recommendation: Based on the findings, it was, therefore, included in the recommendations that to successfully incorporate ICT into teaching and learning, policymakers must offer the essential teaching and learning tools to teachers.